IS REASONING BY ANALOGY CENTRAL TO LEGAL REASONING? (NATIONAL CAPITAL LAW JOURNAL, 2000)
NA
Keywords: Reasoning By Analogy; Legal Reasoning; Judicial Decision-Making; Doctrine Of Precedent; Analogical Arguments; Legal Principles; Common Law Adjudication; rule Application; Legal Interpretation; Judicial Law-Making; Judicial Law